2022
DOI: 10.1021/acspolymersau.2c00021
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Predictors of Knotted and Linked Arcs

Abstract: Inspired by how certain proteins "sense" knots and entanglements in DNA molecules, here we ask if there exist local geometric features that may be used as a read-out of the underlying topology of generic polymers. We perform molecular simulations of knotted and linked semiflexbile polymers and study four geometric measures to predict topological entanglements: local curvature, local density, local 1D writhe and non-local 3D writhe. We discover that local curvature is a poor predictor of entanglements. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…However, one can consider other rotational invariant features. For instance, a recent work 63 suggested that the local density along the ring (i.e., the average number of neighboring beads) could be a set of rotational and translational features that can faithfully capture the underlying topology of the rings.…”
Section: Discussionmentioning
confidence: 99%
“…However, one can consider other rotational invariant features. For instance, a recent work 63 suggested that the local density along the ring (i.e., the average number of neighboring beads) could be a set of rotational and translational features that can faithfully capture the underlying topology of the rings.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we set out to test the use of a different type of geometric feature that our group recently utilised to identify essential crossings of a knot and plectoneme-like double folding of ring polymers. 25,26 More specifically, we focused on a generalisation of the Gauss linking integral applied to a single closed curve, often associated with its writhe 27 and average crossing number. 25,28 This choice is inspired by the intuition that writhe captures the geometrical entanglement of a curve with itself, and we thus define a generalised local segment-to-segment (StS) writhe aswhere r ( x ) and t ( x ) are the 3D position of, and the tangent at, segment x , respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 23 since we use a smaller training dataset and simpler NNs. We then trained the same NNs using a range of other geometric features, such as local curvature, density and 1D writhe 26 (see ESI † for details), and found that most of them performed more poorly, or at best equally, with respect to the XYZ representation ( Fig. 1(E) ).…”
Section: Resultsmentioning
confidence: 99%
“…Equally, these methods have been used to study phase and structural transitions in polymer nanocomposites, [224] to respectively identify the two-state and three-state phase transitions of polymers adsorbed on homogeneous patterned and striped-patterned surfaces, [225] and to identify various knot types in polymers. [226][227][228][229] Furthermore, some researchers have combined ML with traditional simulation methods to enhance the efficiency of relevant processes. Bhattacharya et al [230] developed a universal artificial intelligence tool, called dPOLY, for analyzing MD trajectories and predicting phase and phase transitions in polymers.…”
Section: Phase Classificationmentioning
confidence: 99%